Effect of forming speeds on coil-break formation during uncoiling of fully annealed low carbon steel sheets-a 3D finite element simulation study / Kam Weng Joe - Kam , Weng Joe (2022)
Coil breaks are narrow, irregularly changing deformation lines that causes difficulties in many steel industries as it is considered as a serious surface defect which leads to esthetical problems on the final product. A 3D explicit finite element model was developed to evaluate the coil break formations during uncoiling of full annealed low carbon steel sheets at different speeds. The 3D model consists of 2 lap coils measuring 600 mm in the inner core diameter and 300 mm width with a sheet thickness of 1.5 mm. The line speed was increased from 1 mpm to 1000 mpm and the change in true (LE11) strains and stress distributions (S11) along the longitudinal direction on top surface of the sheet were recorded. The simulation results show that there are 7 interruption zones with Zone A consists of narrow band of compressive strain and Zone B which consists of islands of tensile strain or coil breaks. The strain rate of the uninterrupted element increased the highest from 0.0007 to 1.1920 /s when the uncoiling speed increased from 1 mpm to 1000 mpm. The higher strain rate will cause the LE11 to reduce which minimizes the peak height. Hence, coil break was able to minimize with 1000 mpm as it subjected to a higher strain rate. Coil tensions were varied from 36 N/mm to 176 N/mm to further reduced the coil break with 1000 mpm line speed. 1000 mpm with coil tension of 146 N/mm was selected as the optimum profile as the severity of the coil breaks are the lowest. In the mesh analysis using higher integration points, the formation of coil break in Zone B1 were eliminated and the severity of coil breaks were increased as more accurate results were obtained. The total computational time recorded for 1000 mpm with coil tension of 146 N/mm with 7 integration points was 0.38 hours (22.8 minutes).